The fluid and transcultural self: renegotiating the East Asian female identity in The Clay Marble by Minfong Ho - Syamsina Zahurin Shamsuddin,; Ida Baizura Bahar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines how the contemporary Chinese-American author Minfong Ho (b. 1951) portrays Dara, the female protagonist of The Clay Marble (1991), in her practice of culture in Cambodian society in order to explore the Western perspective of the East Asian female identity as voiceless, submissive and hypersexual. Using the concepts of identity fluidity as proposed by the sociologist and cultural theorist Stuart Hall (2011) and his views on the decentring of the individual, the paper aims to investigate how the three concepts of the enlightenment subject, the sociological subject and the postmodern subject interact with Arianna Dagnino’s (2015) concept of transculture/ality, or intermingling of cultures, in The Clay Marble through Dara’s practice of culture in Cambodian society and how she is decentred as her identity evolves. Ho’s portrayal of Dara reveals an East Asian female who experiences identity fluidity in her thinking, attitude and behaviour while her stable, regular and fixed self in the enlightenment subject phase becomes decentred through transculture/ality at the sociological subject phase. Here, through transculture/ality, or her interaction or communication within her culture, she links herself to society and transforms as she finds her voice and manifests individual agency. By doing so, Dara enters the third phase, the postmodern subject, where her thinking, attitude and behaviour are constantly changing as are the ways in which she is defined and addressed in her Cambodian culture.